ДЕРИВАТОЛОГИЯ НАЗАРИЙ ТИЛШУНОСЛИКНИНГ МУСТАҚИЛ СОҲАСИ СИФАТИДА - Даниева, М.Д. (SCIENCE and SOCIETY, 2019)
The article provides information on formation, development and evolution of derivatology as a science. The article also focuses on the structural-semantic construction of word combinations changes in the derivative process as well as aspects related to language system dynamics. The analysis of the derivative features of word combinations is based on the ideas of the famous linguists.
Keywords: unit; oral speech; derivatology; grammar; source; process; linguistics; system; syntactic; semantic